Increasing reactivity by incorporating π-acceptor ligands into coordinatively unsaturated thiolate-ligated iron(II) complexes - Toledo, Santiago (Inorganica Chim Acta, 2021)
Reported herein is the structural, spectroscopic, redox, and reactivity properties of a series of iron complexes containing both a π-donating thiolate, and π-accepting N-heterocycles in the coordination sphere, in which we systematically vary the substituents on the N-heterocycle, the size of the N-heterocycle, and the linker between the imine nitrogen and tertiary amine nitrogen. In contrast to our primary amine/thiolate-ligated Fe(II) complex, [Fe(II)(S(Me2)N(4)(tren))](+) (1), the Fe(II) complexes reported herein are intensely colored, allowing us to visually monitor reactivity. Ferrous complexes with R = H substituents in the 6-position of the pyridines, [Fe(II)(S(Me2)N(4)(6-H-DPPN)](+) (6) and [Fe(II)(S(Me2)N(4)(6-H-DPEN))(MeOH)](+) (8-MeOH) are shown to readily bind neutral ligands, and all of the Fe(II) complexes are shown to bind anionic ligands regardless of steric congestion. This reactivity is in contrast to 1 and is attributed to an increased metal ion Lewis acidity assessed via aniodic redox potentials, E(p,a), caused by the π-acid ligands. Thermodynamic parameters (ΔH, ΔS) for neutral ligand binding were obtained from T-dependent equilibrium constants. All but the most sterically congested complex, [Fe(II)(S(Me2)N(4)(6-Me-DPPN)](+) (5), react with O(2). In contrast to our Mn(II)-analogues, dioxygen intermediates are not observed. Rates of formation of the final mono oxo-bridged products were assessed via kinetics and shown to be inversely dependent on redox potentials, E(p,a), consistent with a mechanism involving electron transfer.